Sigi Kelengkapan Media Pembelajaran Geografi pada SMA Negeri di Palangka Raya - Eri Puspita Dewi; Krisma Natalia; Teguh Pribadi (Media Komunikasi Geografi, 2018)
This study was conducted to analyze the geographical learning media completeness (GLMC). Eight public senior high schools (PSHS) were surveyed from August to September 2015. GLMC questionnaire used to explore those data. Descriptive statistics used to reveal school characteristics and GLMC. Cross-tabulation with chi-square analysis applied to measure not only school accreditation (SA) but also school quality (SQ) with GLMC. GLMC at PSHA in Palangka Raya were less full criteria. Software, laboratory equipment, mock-ups, visual-aids, and specimens were some samples of GLMC rarely found at PSHA in Palangka Raya. SA was not correlated with GLMC (χ2 = 8,533; C = 0,718; df = 4; p = 0,074) so it was SC (χ2 = 2,000; C = 0,447; df = 2; p = 0,368). Nevertheless, PSHA in Palangka Raya had higher SA and SQ indicated qualified GLMC. Apply school facilities and infrastructures management enhanced the quality of the geographical learning media (GLM). Teachers should optimize GLM at school by increasing their information technology literacy and skill.